2021
DOI: 10.30798/makuiibf.821611
|View full text |Cite
|
Sign up to set email alerts
|

Enerji̇ Fi̇yatlari İle Borsa İstanbul Endeksleri̇ Arasindaki̇ İli̇şki̇leri̇n Test Edi̇lmesi̇

Abstract: Oil and natural gas, which are the most used energy sources, are consumed as raw materials in many fields. The development of technology and population increase makes these energy sources important for financial markets and the overall economy. Turkey, energy importing and developing country, maybe influenced intensely by changes in energy prices. In this study, long-term and short-term relationships between energy prices and Borsa Istanbul indices using daily data between 01.01.2007-31.10.2017 were examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Shi and Kong (2021), in their study examining the impact of international crude oil prices on energy stock prices in China during the COVID-19 epidemic, found that COVID-19 significantly strengthened the correlation between the variables and the volatility between oil price returns and energy stock returns has been found to have a spreading effect. Temel and Eryiğit (2021), in their study investigating the relationships between energy prices and various BIST indices using daily data between January 1, 2007 and October 31, 2017, did not find a long-term relationship between energy prices and indices. In the short term, they determined that energy prices had a positive effect on BIST indices.…”
Section: Golder Et Al (2020) Used the Johansen Cointegration Test Thementioning
confidence: 94%
“…Shi and Kong (2021), in their study examining the impact of international crude oil prices on energy stock prices in China during the COVID-19 epidemic, found that COVID-19 significantly strengthened the correlation between the variables and the volatility between oil price returns and energy stock returns has been found to have a spreading effect. Temel and Eryiğit (2021), in their study investigating the relationships between energy prices and various BIST indices using daily data between January 1, 2007 and October 31, 2017, did not find a long-term relationship between energy prices and indices. In the short term, they determined that energy prices had a positive effect on BIST indices.…”
Section: Golder Et Al (2020) Used the Johansen Cointegration Test Thementioning
confidence: 94%